Effect of perindopril or leucine on physical performance in older people with sarcopenia: the LACE randomized controlled trial. Issue 2 (16th February 2022) - ,; Achison, Marcus; Adamson, Simon; Akpan, Asangaedem; Aspray, Terry; Avenell, Alison; Band, Margaret M.; Bashir, Tufail; Burton, Louise A.; Cvoro, Vera; Donnan, Peter T.; Duncan, Gordon W.; et al.
Abstract: Background: This trial aimed to determine the efficacy of leucine and/or perindopril in improving physical function in older people with sarcopenia. Methods: Placebo‐controlled, parallel group, double‐blind, randomized two‐by‐two factorial trial. We recruited adults aged ≥ 70 years with sarcopenia, defined as low gait speed (<0.8 m/s on 4 m walk) and/or low handgrip strength (women < 20 kg, men < 30 kg) plus low muscle mass (using sex and body mass index category‐specific thresholds derived from normative UK BioBank data) from 14 UK centres. Eligible participants were randomized to perindopril 4 mg or placebo, and to oral leucine powder 2.5 g or placebo thrice daily. The primary outcome was the between‐group difference in the short physical performance battery (SPPB) score over 12‐month follow‐up by repeated‐measures mixed models. Results were combined with existing systematic reviews using random‐effects meta‐analysis to derive summary estimates of treatment efficacy. Results: We screened 320 people and randomized 145 participants compared with an original target of 440 participants. For perindopril [ n = 73, mean age 79 (SD 6), female sex 39 (53%), mean SPPB 7.1 (SD 2.3)] versus no perindopril [ n = 72, mean age 79 (SD 6), female sex 39 (54%), mean SPPB 6.9 (SD 2.4)], median adherence to perindopril was lower (76% vs. 96%; P < 0.001). Perindopril did not improve the primary outcome [adjusted treatment effect −0.1 points (95%CI −1.2 to 1.0), P = 0.89]. No significant treatment benefit was seen for any secondary outcome including muscle mass [adjusted treatment effect −0.4 kg (95%CI −1.1 to 0.3), P = 0.27]. More adverse events occurred in the perindopril group (218 vs. 165), but falls rates were similar. For leucine [ n = 72, mean age 78 (SD 6), female sex 38 (53%), mean SPPB 7.0 (SD 2.1)] versus no leucine [ n = 72, mean age 79 (SD 6), female sex 40 (55%), mean SPPB 7.0 (SD 2.5)], median adherence was the same in both groups (76% vs. 76%; P = 0.99). Leucine did not improve the primary outcome [adjusted treatment effect 0.1 point (95%CI −1.0 to 1.1), P = 0.90]. No significant treatment benefit was seen for any secondary outcome including muscle mass [adjusted treatment effect −0.3 kg (95%CI −1.0 to 0.4), P = 0.47]. Meta‐analysis of angiotensin converting enzyme inhibitor/angiotensin receptor blocker trials showed no clinically important treatment effect for the SPPB [between‐group difference −0.1 points (95%CI −0.4 to 0.2)]. Conclusions: Neither perindopril nor leucine improved physical performance or muscle mass in this trial; meta‐analysis did not find evidence of efficacy of either ACE inhibitors or leucine as treatments to improve physical performance.